2016
DOI: 10.1002/2015gc005941
|View full text |Cite
|
Sign up to set email alerts
|

Applications of detrital geochronology and thermochronology from glacial deposits to the Paleozoic and Mesozoic thermal history of the Ross Embayment, Antarctica

Abstract: Till from moraines at the heads of six major outlet glaciers in the Transantarctic Mountains (TAM) and from till beneath three West Antarctic ice streams have a ubiquitous zircon U‐Pb age population spanning the time of the Ross/Pan‐African Orogenies (610–475 Ma). Geochronology and thermochronology of detrital minerals in these Antarctic glacial tills reveal two different thermal histories for the central and southern TAM. Double‐dating of the zircons reveals a geographically widespread (U‐Th)/He (ZHe) populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 79 publications
2
16
0
Order By: Relevance
“…Some of the analyzed samples do, however, record rapid cooling as early as 120 Ma. A similar timing has been identified by Welke et al [] in the Ross Sea embayment of West Antarctica from zircon helium dating of detrital samples, which show a dominant age population of 180 to 130 Ma. Based on that, Welke et al [] infer a Gondwana breakup related exhumation event for this section of the Transantarctic Mountains.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Some of the analyzed samples do, however, record rapid cooling as early as 120 Ma. A similar timing has been identified by Welke et al [] in the Ross Sea embayment of West Antarctica from zircon helium dating of detrital samples, which show a dominant age population of 180 to 130 Ma. Based on that, Welke et al [] infer a Gondwana breakup related exhumation event for this section of the Transantarctic Mountains.…”
Section: Discussionsupporting
confidence: 85%
“…A similar timing has been identified by Welke et al [] in the Ross Sea embayment of West Antarctica from zircon helium dating of detrital samples, which show a dominant age population of 180 to 130 Ma. Based on that, Welke et al [] infer a Gondwana breakup related exhumation event for this section of the Transantarctic Mountains. At that time, the Zealandia crustal blocks (including Campbell Plateau, Chatham Rise, North Island, and South Island; Figure S1) were still contiguous with West Antarctica and subduction of Phoenix Plate beneath the eastern Gondwana margin was still ongoing.…”
Section: Discussionsupporting
confidence: 85%
“…Interpretations of Beacon sediment provenance were initially derived from paleocurrent indicators, and subsequent work on detrital zircon U-Pb ages in these rocks have confirmed inputs from both East and West Antarctic sources (Elliot and Fanning, 2008;Elsner et al, 2013;Elliot et al, 2014). Beacon-derived zircons appear to constitute a significant fraction of zircons in Quaternary tills from the Transantarctic Mountains (Licht et al, 2014;Welke et al, 2016).…”
Section: What Is the Geology Of Antarctica That Makes This Possible?mentioning
confidence: 96%
“…The double-or triple-dating of individual detrital zircon grains provides powerful insight into the geologic history of sediments' sources (e.g., Reiners, 2005;Tochilan et al, 2012;Thomson et al, 2013;Welke et al, 2016). No single grain of sand in glacigenic sediment must be from the same source as any other single grain, but any chronometer or geochemical tracer in a single grain must have experienced the same geological history.…”
Section: Zirconmentioning
confidence: 99%
“…Palmer et al (2012) showed that nunatak moraines can be valuable repositories of previously unknown bedrock buried beneath the ice sheet. The erratics and detrital minerals transported by ice and finally deposited in moraines can be used to make inferences about unexposed geologic terrains (e.g., Welke et al, 2016).…”
Section: Introductionmentioning
confidence: 99%